Using corporate Governance Mechanisms to Reduce Earnings Management under agency theory - Natiq Jabbar Salem; Haider Atta Zbain; Nawfal Hussein Abdullah (Journal of Madenat Alelem University College, 2021)
The research attempts to show role of corporate governance to limit earnings management according to theory of agency by using governance technics whether internal or external, also many corporate managements attempt to exploit  powers given for it to show positive aspects about management of those corporates, and good appearance in front of the owners through manipulation of profits because result of the selection specific financial and accounting policies show the financial position of the corporate in the short term exploiting the flexibility in accounting standards to choose a particular method of accounting treatment and disclosure in the financial statements. To limit these actions, the owners should follow several technics to reduce conflicts of interest between managers and owners, the manipulation of financial and accounting policies, and the persistence of using these policies.